Swedish Bird Survey: Swedish coastal bird monitoring programme (Nationella kustfågelövervakningen) - Fredrik Haas; Martin Green (Lund University, 2021)
The Swedish coastal bird monitoring programme (aka the ”Archipelago squares”/”Kustfågelrutorna”) is one of several schemes within the Swedish Bird Survey (see below), run by the Department of Biology at Lund University.

The survey scheme was initiated in 2015 as a standardized method for detecting and reporting changes in the abundance of coastal and archipelagic birds and their distributions in Sweden over time.

The 200 archipelago squares are distributed along the Swedish coastline and are surveyed during the breeding season.

In this dataset, some information is placed in the table ExtendedMeasurementOrFacts (eMoF), which is part of the Source Archive available to download directly from the dataset’s page here on gbif.org. The Source Archive contains the data exactly as uploaded to gbif (verbatim). Should you choose to download the dataset as GBIF Annotated Archive instead, the data has been interpreted and quality controlled by gbif, but, the data in the eMoF will not be included as the eMoF extension is not yet supported by gbif.
Keywords: Samplingevent; SAMPLING_EVENT; Biological Sciences; Biologi